DNA Mismatch Repair Gene Variants in Sporadic Solid Cancers - Caja, Fabian; Vodickova, Ludmila; Kral, Jan; Vymetalkova, Veronika; Naccarati, Alessio; Vodicka, Pavel (International journal of molecular sciences, 2020)
The phenotypic effects of single nucleotide polymorphisms (SNPs) in the development of sporadic solid cancers are still scarce. The aim of this review was to summarise and analyse published data on the associations between SNPs in mismatch repair genes and various cancers. The mismatch repair system plays a unique role in the control of the genetic integrity and it is often inactivated (germline and somatic mutations and hypermethylation) in cancer patients. Here, we focused on germline variants in mismatch repair genes and found the outcomes rather controversial: some SNPs are sometimes ascribed as protective, while other studies reported their pathological effects. Regarding the complexity of cancer as one disease, we attempted to ascertain if particular polymorphisms exert the effect in the same direction in the development and treatment of different malignancies, although it is still not straightforward to conclude whether polymorphisms always play a clear positive role or a negative one. Most recent and robust genome-wide studies suggest that risk of cancer is modulated by variants in mismatch repair genes, for example in colorectal cancer. Our study shows that rs1800734 in MLH1 or rs2303428 in MSH2 may influence the development of different malignancies. The lack of functional studies on many DNA mismatch repair SNPs as well as their interactions are not explored yet. Notably, the concerted action of more variants in one individual may be protective or harmful. Further, complex interactions of DNA mismatch repair variations with both the environment and microenvironment in the cancer pathogenesis will deserve further attention.
Keywords: cancer; genotype; Disease Progression; jednonukleotidový polymorfismus; progrese nemoci; MutL Protein Homolog 1; oprava chybného párování bází DNA; single nucleotide polymorphism; MutL homolog 1; Neoplasms; treatment outcome; homolog 2 proteinu MutS; DNA Mismatch Repair; genetic variants; Humans; metylace DNA; nádory; DNA Methylation; mismatch repair; genes; MutS Homolog 2 Protein; patients; zárodečné mutace; Germ-Line Mutation; lidé; Polymorphism, Single Nucleotide